2020
DOI: 10.1002/pat.5192
|View full text |Cite
|
Sign up to set email alerts
|

An effective method for delayed migration of dripping agent from linear low‐density polyethylene films

Abstract: Dripping agents are incorporated into polyethylene films to improve the hydrophility of the film surface and minimize the effects of fogging. A reactive‐type of dripping agent, 18,alkyl diethanolamine acrylic monoester (EDM), was synthesized and then grafted onto layered double hydroxides (LDHs) to delay its migration, which is due to the large size of LDHs. Then, the LDH‐g‐EDM compound was added to linear low‐density polyethylene (LLDPE), and dripping films were prepared for studying their properties. Mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The L1 film had a 38° contact angle, which was smaller than that of the L0 film. The addition of GMS significantly reduced the contact angle of the LLDPE film due to the strong hydrophilicity of the −OH groups of GMS . In addition, according to Wenzel’s correction to Young’s equation, the surface was hydrophilic if the contact angle was less than 90°.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The L1 film had a 38° contact angle, which was smaller than that of the L0 film. The addition of GMS significantly reduced the contact angle of the LLDPE film due to the strong hydrophilicity of the −OH groups of GMS . In addition, according to Wenzel’s correction to Young’s equation, the surface was hydrophilic if the contact angle was less than 90°.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of GMS significantly reduced the contact angle of the LLDPE film due to the strong hydrophilicity of the −OH groups of GMS. 48 In addition, according to Wenzel's correction to Young's equation, the surface was hydrophilic if the contact angle was less than 90°. At this time, the increase of film surface roughness will enhance the resistance caused by the multistage gradient diffusion of water droplets, it could reduce the contact angle with the film, and the surface was more hydrophilic.…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…16 At present, there are many ways to delay the migration of antifogging agents in polyethylene films. Yang et al 17 have grafted a reactive-type antifogging agent C18 alkyl diethanolamine acrylic monoester (EDM) onto layered double hydroxide (LDH). Accelerated dripping experiments at 60 °C have shown that the dripping duration of the LLDPE/ LDH-g-EDM film is up to 18 days with 2 wt % EDM and 0.6 wt % LDH, which is 7 days longer than that of a control LLDPE/LDH film.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many ways to delay the migration of antifogging agents in polyethylene films. Yang et al . have grafted a reactive-type antifogging agent C18 alkyl diethanolamine acrylic monoester (EDM) onto layered double hydroxide (LDH).…”
Section: Introductionmentioning
confidence: 99%